Effects of metoclopramide on Vmax of action potentials in guinea pig papillary muscles - LU Xiao-dong; ZHAO Geng-sheng (Acta Pharmacologica Sinica, 2016)
The effects of metoclopramide (MCP) on Vmax of action potentials of guinea pig papillary muscles were studied with intracellular microelectrodes. MCP 10-550 mumol/L abbreviated the action potential duration at 90% repolarization (APD90) and decreased the maximal rate of rise of action potential (Vmax) dose-dependently. MCP caused rate-dependent and voltage-dependent reductions of Vmax and retardation of the recovery of Vmax. The results present the possible causes of depressant effect of MCP on Na channel.